O teritorialnosti in manjšinah - Bufon, Milan (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
The article deals with the concept and meaning of territoriality, and in particular with the relationship between territoriality and European minorities. The author bases his observations on his own research and theoretical discussions provided by international scholars, and suggests that the relationship between territoriality and minorities is embedded in a wider process of transformation of areas of social and cultural contact. The very concept and the differentiation of autochthonous minorities, in particular between national and regional minorities, could be understood in such a context as the result of social modernization and territorialisation in the classic period of European nationalism. The spatial dimension of minorities has with progress significantly changed, producing also important changes to inter-ethnic relations and opportunities for the development of minority protection measures. Here, different approaches could be adopted, ranging from classic non-territorial and territorial to current integrative concepts, the latter aiming to harmonize socio-cultural diversity with a growing quest for social (re)integration and re-construction of European multicultural landscapes.
Keywords: teritorialnost; narodne manjšine; regionalne manjšine; kulturne pokrajine; nacionalizem; nationalism; integracija